دور شركات المساهمة في إصدار وتداول الأسهم في سوق رأس المال الإسلامي - مسعـودة, نصبه (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES)
تلعب شركات المساهمة دورا مهما في سوق رأس المال الإسلامي حيث تمنع من لجوء المسلم إلى إقراض ماله بالربا،كما تعمل على حفز وتشجيع المدخرات الصغيرة على المشاركة في إنشاء المشاريع الحيوية فانضمام رأس المال القليل إلى مثله يجعله كثيرا وهو ما يساهم في بناء المجتمع وازدهاره، وهذا من خلال إصدار الأسهم وتداولها، وكان لزاما وضع ضوابط شرعية تحكم عمل هذه الشركات، إذ لا يجوز القول بجواز التعامل بالأسهم دون التفريق بين أنواعها وآلية عملها وطبيعتها، فبعض أنواع الأسهم يدخلها الربا، وبعضها تصدره شركات ذات أغراض غير مشروعة وبعضها ذات أغراض مشروعة، وأخرى مختلطة.         joint-stock companies play an important role in the Islamic capital market, where barred from asylum-Muslim to lend money with interest, is also working to stimulate and encourage small savings to participate in the establishment of vital projects's accession capital little to like it a lot, which contribute to the building and prosperity of society and this through the issuance and trading of shares, and had to put controls the legitimacy of governing the work of joint stock companies, it may not be that it is permissible to deal with shares without differentiating between the types and mechanism of action and nature, some types of shares are tapped by usury, and some are issued by companies for illicit purposes and some of which are legitimate purposes, and other mixed .